Innovation and Employment: Evidence from Italian Microdata - Mariacristina Piva; Marco Vivarelli (Institute for the Study of Labor (IZA), 2003)
The microeconomic empirical literature devoted to the link between innovation and employment tends to suggest that technological change has a positive effect on jobs, at least at the level of the firm. The main purpose of this paper is to see whether this result still holds in a situation where intermediate technologies are implemented mainly through gross innovative investments, as in Italian manufacturing. Applying GMM-SYS to an employment equation augmented for technology and using a unique longitudinal dataset of 575 Italian manufacturing firms over the period 1992-1997, this paper finds a significant - although small in size - positive relationship between innovation and employment. While the links with sales and wages have the expected signs and turn out to be significant, the job creating impact of innovation proves robust after checking for time, industry, firm's size and geographical fixed effects.
Keywords: O33; 330; technology; employment; Italian manufacturing; GMM-SYS; Innovation; Angepaßte Technologie; Beschäftigungseffekt; Schätzung; Momentenmethode; Italien; GMM-SYS